The Orthophotomap of Lublin 1944: from Luftwaffe photographs to map application – idea, methods, contemporary challenges of processing and publishing archival aerial photographs - Kuna Jakub (Polish Cartographical Review, 2022)
The origins of aerial photography can be traced back to the second half of the 19th century, and periods of World Wars contributed to the development of techniques for developing and disseminating aerial photographs for military purposes. In the literature, we find descriptions of the Polish Military Geographical Institute’s (WIG) use of aerial photography to update topographic maps of nearly 40% of the country’s area at the time. Unfortunately, the fate of the pre-war collection of photographs is difficult to establish. Given this, the aerial photographs from the period of the Second World War (German and Allied) constitute the oldest possible complete and consistent photographic documentation of Poland. The series of German prints (373-GXPRINTS) collected at the National Archives and Records Administration in College Park (NARA, USA) are maintained according to the most liberal policy on access and further use. At the same time, the organisation of the NARA archive and the extent to which the collection has been digitised (over one million images) leave a deficiency, and searching for images requires knowledge, methods and experience.